2010
DOI: 10.1097/psy.0b013e3181c932d4
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Design of a Randomized Clinical Trial Comparing Stress Reduction Treatment to Usual Cardiac Care: The Reducing Vulnerability to Implantable Cardioverter Defibrillator Shock-Treated Ventricular Arrhythmias (RISTA) Trial

Abstract: Objective-Present the design of a multicenter randomized trial testing the effects of Stress Reduction Treatment (SRT) on the prevalence of shock treated ventricular arrhythmias among patients with an implantable cardioverter defibrillator (ICD). Significant adjustment problems secondary to ICD shock can increase the likelihood of arrhythmias requiring shock for termination. Whether SRT can reduce arrhythmias requiring shock for termination in patients with ICDs has not been tested in clinical trials.Methods-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Although these studies, taken together, suggest that CBT is not associated with reduced arrhythmia events, it is important to note that arrhythmia events were defined as those triggering an ICD therapy, and thus, arrhythmia events below the treatment threshold would be missed. Studies to better address arrhythmia outcomes of CBT are underway (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies, taken together, suggest that CBT is not associated with reduced arrhythmia events, it is important to note that arrhythmia events were defined as those triggering an ICD therapy, and thus, arrhythmia events below the treatment threshold would be missed. Studies to better address arrhythmia outcomes of CBT are underway (5).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated depressive and anxiety symptoms (2)(3)(4), in turn, are associated with an increased risk of arrhythmia events necessitating ICD therapies. The high occurrence rate of psychological problems and the potential detrimental effects on cardiac function underscore the need for psychosocial interventions that can help individuals optimize adaptation to the ICD and possibly prevent emotionally triggered ventricular arrhythmias necessitating ICD shock therapy (5).…”
Section: Introductionmentioning
confidence: 99%
“…Even though some of these trials are plagued by methodological short comings, they show that multifactorial interventions are likely to be the most successful, including for example cognitive behavioral therapy, psycho-education about the ICD and cardiac rehabilitation as some of the mainstay components [85], which can, if warranted, be combined with pharmacological treatment. Other trials with the aim to improve mental health outcomes in ICD patients are currently underway that use comprehensive and state-of-the-art techniques in behavioral medicine, including e-health [86,87]. …”
Section: Five-year Viewmentioning
confidence: 99%
“…The largest study to date of a stress reduction therapy is ongoing, using a cognitive-behavioral model of stress that emphasizes the interactive relationship of cognition, emotion, physiology, and behavior (Reducing Vulnerability to ICD Shock Treated Arrhythmia [RISTA]). 21 Whether interventions should be offered to all ICD patients, or are of most benefit in subgroups demonstrating distress at baseline, is an important avenue of future research.…”
Section: Psychosocial Impact Of the Icdmentioning
confidence: 99%
“…One small study (N=70) found a positive effect of cognitive therapy on ICD-treated ventricular arrhythmias at 3 months. 31 The larger ongoing RISTA study described above 21 is powered to investigate the effects of a stress management intervention on receipt of appropriate ICD therapy as a primary end point.…”
Section: Immediate and Long-term Approach To The Patient With Shocksmentioning
confidence: 99%